STRATEGI SINGLE PARENT DALAM PEMENUHAN KEBUTUHAN EKONOMI KELUARGA (Studi 5 Single Parent di Nagari Balun Kecamatan Koto parik Gadang di Ateh Kabupaten Solok Selatan) - MONALISA, IIN - (Pendidikan Sosiologi, 2014)
In general, a family consisting of father mother and child. The family has thefunction dang responsibilities that must be followed, providing the necessaryeducational and economic needs of the child, in contrast to the reality in Bagaribalun that there are 20 people who holds the status of single parent where a singleparent in addition to functioning as a mother of two also serves as head of thefamily, he also had to meet the economic needs of their families in accordancewith the above subject matter, the research problem is formulated as follows: (1)how the economic conditions of single parent families in Nagari balun? (2) whateconomic strategy in Nagari Balun single parent in meeting the needs of theeconomy?.In this study, the authors used the theory of Social Action by Max Weber,in which Weber saw social reality (society) as being based on the motivations ofindividual and social actions. A single parent doing an action in family economicneeds. The approach used in the study are in qualitative research methods, whichapproach intends to make a solid assessment. While the type of research that isdescriptive to provide a detailed description of the reality studied. Taking researchinformants by purposive sampling, informants in this study consisted of 5 people.The type of data collected is primary and secondary data. Data was collectedthrough observation, interviews and document study. The unit of analysis inresearch in individual dalah consists of 5 single parent. Analysis of the data usingthe model of Miles and Huberman, namely data collection, data presentation andconclusion.The results of this study indicate that the economic condition of singleparent families in Nagari Balun include economic conditions, including the singleparent family is simple and there is also capable of that single parent must stillmeet the needs of their children even in conditions of the underprivileged.Sedangkanstrategi single parent in Nagari balun in meeting the needs of theeconomy are looking for a side job as well as the loan of the Village cooperatives.